Former Yugoslav Republic of Macedonia : Climate Change and Agriculture Country Note - World Bank (Washington, DC, 2015)
This country note for Macedonia is part of a series of country briefs that summarize information relevant to climate change and agriculture for four pilot countries in the Europe and Central Asia (ECA) Region, with a particular focus on climate and crop projections, adaptation options, policy development and institutional involvement. The note series has been developed to provide a baseline of knowledge on climate change and agriculture for the pilot countries participating in the regional program on reducing vulnerability to climate change in ECA agricultural systems. This note for Macedonia was shared with the Government and other agricultural sector stakeholders and used as an engagement tool for a National Awareness Raising and Consultation Workshop, held in Skopje in May 2010. Feedback and comments on the note from this consultation process have been incorporated into this updated version in collaboration with the Macedonian Ministry of Agriculture, Forestry and Water Economy (MAFWE).